NUMERICAL ANALYSIS AND EXPERIMENTAL STUDY ON THE RACK OF MASSAGE CHAIR - ZHANG DongDong; QIN BaoRong; WANG ZhengXing; XIANG BingLe; ZHOU Hui; DAI ZeBin (Jixie qiangdu)
Aiming at the people’s requests of comfort and functions,a rack of massage chair was designed. Numerical analysis was done based on the three-dimensional model. Kinematic simulation was run on the virtual prototype model based on the ADAMS software,the functions was verified and the theoretical basis was supported for the choose of the electric putter.Finite element analysis was done on the key components of the structure under the environment of ANSYS Workbench,the strength and stiffness were checked. Experimental study was done after the prototypes were made. The research results indicate that the rack can meet the function requests of zero gravity and zero against the wall. The strength and stiffness of the structure can meet the requests of the testing standard. The experimental results consistent with the numerical analysis results. That verifies the validity of numerical analysis. The research results also offer important basis for the later structure optimization.